Exploring the struggles of unrecognized female farmers: a gender analysis at Kaunia upazila, Rangpur (Research in Agriculture Livestock and Fisheries, 2023)
This research focuses on the gender differences in agriculture in the village of Baje Mazkur in Kaunia Upazila. It demonstrates gender disparities in agriculture and elucidates the factors which prevent female farmers from receiving adequate recognition in a variety of ways in the study region. The study used a qualitative method to collect data and data has been analyzed from gender perspectives. To understand the work nature of female farmers, their struggles, and the reason for unrecognition the Agrarian Ideology and The Longwe Framework have been used. It shows that female farmers in the study area engage themselves in a variety of farming activities but their contribution to agriculture is viewed solely as family responsibilities where women are not recognized for their contribution. Female farmers are often unable to utilize their full potential because they are denied various extension services or support from government and non-government organizations. The findings also show that a lack of access to land, finance, and other resources are the most significant barriers to female farmers. Though the situation is gradually improving, women farmers continue to be paid less than men.Vol. 10, No. 1, April 2023: 09-19